2018
DOI: 10.3390/su10103375
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Conservation Agriculture in Uganda: A Case Study of the Lango Subregion

Abstract: Conservation agriculture (CA) is based on three principles: minimum soil disturbance, maintaining a soil cover through mulching with crop residues or planting cover crops, and practicing crop rotations. CA is practiced in many parts of the world for its benefits to soil and ability to improve yields, among others. There is little documented information on the status of CA adoption in the Lango region in mid-Northern Uganda. This study aimed at determining the extent of CA adoption in relation to the socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The existing literature reports that sustainable intensification practices (SIPs) have supported many communities in refining their resources and enhancing production [20]. The diffusion and adoption of modern sustainable agriculture practices among developing countries still stay lower than the desired levels [8,[21][22][23][24][25]. Multiple authors have conducted studies to investigate the underlying reasons for the low adoptions.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature reports that sustainable intensification practices (SIPs) have supported many communities in refining their resources and enhancing production [20]. The diffusion and adoption of modern sustainable agriculture practices among developing countries still stay lower than the desired levels [8,[21][22][23][24][25]. Multiple authors have conducted studies to investigate the underlying reasons for the low adoptions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies across the African continent indicated that socio-economic factors, farm characteristics and agro-climatic zone characteristics were the main factors influencing adoption of SAPs by smallholder farmers [18][19][20][21]. Therefore, factors influencing adoption of SAPs varies with countries and regions as a result of differences in cultural and political ideologies, natural resources community access to education, adequate information on the technical details of the SAPs, extension services, credits and infrastructure [13,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Surveys containing fixed-response questions were administered to local landowners orally in Spanish using local translators. Data collection followed cluster and snowball sampling methods, which utilized expert input from staff at the Organization for Tropical Studies (OTS) for identifying forest fragments for sampling (Bolt et al, 2018;Kaweesa et al, 2018). At these selected sites, every surrounding residence was approached to take the survey.…”
Section: Participation In Conservation Strategiesmentioning
confidence: 99%